A rare case of late‐onset limb‐girdle muscular dystrophy: Calpainopathy. Issue 3 (29th July 2022) - Painkra, Bhawana; Mallick, Richa; Das, Sumanta; Kumar, Pramod; Chatterjee, Prasun
Abstract : Limb‐girdle muscular dystrophy is a genetic disorder usually presenting in younger age patients. This case report presents a case of late‐onset limb‐girdle muscular dystrophy type R1 (Calpainopathy) in a 65 year old patient.